PENGARUH PENERAPAN MEDIA PEMBELAJARAN KARTU KATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS II SDN NO 196 INPRES BONTOMAJANNANG KECAMATAN GALESONG UTARA KABUPATEN TAKALAR - Wahyuni; Rohana; Yusnadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the low initial reading ability of class II students at SDN No. 196 Inpres BontomajannangKecamatan Galesong Utara Kabupaten Takalar. This research aims to (1) determine the application of word card learning media to the beginning reading abilities of class II students at SDN No 196 Inpres Bontomajannang, (2) find out the description of the beginning reading abilities of class II students at SDN No 196 Inpres Bontomajannang, and (3) find out The influence of word card learning media on initial reading ability in class II students at SDN No. 196 Inpres Bontomajannang. The type of research used is quantitative research using Quasi Experiment. This research uses Nonequivalent Control Group Design which involves two research groups, namely the experimental class and the control class. Determining the sample in this study used purposive sampling, so that class II A was 20 students as the experimental class and class II B was 20 students as the control class. The result data in this research are the results of the pretest and posttest. Data analysis techniques use descriptive statistical analysis and inferential statistical analysis consisting of normality, homogeneity and hypothesis tests. The results of this research show that: (1) the application of word card learning media in the experimental class learning process of class students was implemented well and carried out according to the appropriate stages and had a positive influence, (2) the initial reading ability of class II Experimental students after the application of the media word cards experienced an increase with the average posttest score for the experimental group being greater than the control class, namely 87 > 77.60, and (3) there was an influence of the application of word card learning media on the initial reading ability of class II students at SDN No. 196 Bontomajannang Presidential Decree. It can be concluded that the word card learning media influences the beginning reading ability of class II students at SDN No. 196 Inpres Bontomajannang, Kecamatan Galesong Utara, Kabupaten Takalar.